Quality of prison life of female prisoners in Serbia: key challenges and areas of strength = Kakovost zaporskega življenja obsojenk v Srbiji : ključni izzivi in področja moči - Batrićević, Ana (Revija za kriminalistiko in kriminologijo, 2023)
Despite a range of differences between male and female prisoners, research on the female prison population has been lacking due to their smaller representation worldwide. To address this gap, the study aimed to understand the overall prison experience of female prisoners in Serbia by analysing the quality of prison life and examining various dimensions across five overarching categories of the prison climate. A descriptive and cross-sectional study was conducted using the convenience sample of 91 female prisoners serving prison sentences in the Correctional Institution for Women in Požarevac. The Measuring the Quality of Prison Life (MQPL) survey and a one-way repeated-measures ANOVA with post-hoc Bonferroni adjustments were used. Significant variations in ratings of the prison climate were identified. The overall prison experience was rated relatively low with only one quarter of the sample giving a positive rating. The highest-ranked MQPL dimensions were Prisoner Adaptation and Distress, while the lowest were Well-being, Bureaucratic Legitimacy, Organisation and Consistency, and Decency. The proposed holistic approach with practical interventions offers the potential to enhance prison life quality and support the well-being of female prisoners, who represent a vulnerable and marginalised group in society.